Green, safe, fast, and inexpensive removal of CO2 from aqueous KHCO3 solutions using a nanostructured catalyst TiO(OH)2: A milestone toward truly low-cost CO2 capture that can ease implementation of the Paris Agreement. (November 2018) - Toan, Sam; Lai, Qinghua; O'Dell, William; Sun, Zhao; Song, Huiping; Zhao, Ying; Radosz, Maciej; Adidharma, Hertanto; Russell, Christopher; Yao, Hongbao; Wang, Yujun; Fei, Weiyang; et al.
Abstract: With great effort, the Paris Agreement set goals designed to address climate change, but far more effort will be necessary to meet those goals due to the lack of transformational CO2 capture technologies that are cost-effective. This research is designed to overcome the shortcomings of conventional CO2 capture technologies (i.e. the cost, health impacts, and environmental impacts of amines) by using a titanium oxyhydroxide (TiO(OH)2 ) catalyst and a potassium carbonate/bicarbonate sorbent (K2 CO3 /KHCO3, respectively). Nanostructured TiO(OH)2 as a catalyst is able to accelerate desorption processes; the acceleration of CO2 desorption is of greater significance because the process consumes more energy than the sorption process. Experimental results show that the use of nanostructured TiO(OH)2 increases the amounts of desorbed CO2 by as much as 1200%, if not higher. Cyclic sorption-desorption testing combined with material characterization shows that both catalyst and sorbent are stable even after 50 cycles. One major benefit of the kinetic enhancement from this catalyst/sorbent system is the reduction of temperature needed to desorb CO2 ; waste heat may be sufficient to provide all or most of the energy required for CO2 capture. Thus, the energy cost of CO2 capture will be significantly reduced, which may keep electricity prices low, avoiding a decrease in the global economy in order to avert global climate change impacts. Another significant benefit of this system is that this inorganic system is environmentally safe, clean, and non-carcinogenic. Highlights: An in-depth look at the regeneration mechanism of nanostructured TiO(OH)2 . Inexpensive and inorganic CO2 capturing technology. Mitigated energy consumption necessary for the release of CO2 with nanostructured TiO(OH)2 .